SPACE-TIME DISTRIBUTION OF RAINFALL ANOMALY INDEX (RAI) FOR THE SALGADO BASIN, CEARÁ STATE - BRAZIL - Costa, Juliana Alcântara; Rodrigues, Gláuber Pontes (Ciência e Natura, 2017)
Given the great variability of the precipitation in the Brazilian Northeast, it is necessary to use climate indexes for its monitoring. In this sense, this work aims to present a study of the space-time variation in the rainfall at the Salgado Basin, located in the state of Ceará, using the Rainfall Anomaly Index (RAI) as a tool. In order to do so, daily precipitation data from seven meteorological stations were used for the period between 1974 and 2015. From the data obtained, the RAI was calculated and plotted in spatial distribution maps. It was possible to observe that the rainy season at the basin lasts from January to April, and the driest period of the year lasts from July to October. The historical series presented drier years than rainy ones. A variation in the RAI within the basin was evidenced, and the region corresponding to Chapada do Araripe was wetter. The years with the extreme anomalies were related to sea surface temperature anomaly events, which favored its occurrence.